PENGARUH CAMPURAN PASIR SUNGAI PENGGARON TERHADAP KUALITAS HASIL PEMBUATAN BATA MERAH DI SEPANJANG SUNGAI PENGGARON PEDURUNGAN KIDUL, KECAMATAN PEDURUNGAN KOTA SEMARANG - Julianto, Eko Nugroho (Jurnal Teknik Sipil dan Perencanaan, 2009)
Influence sand mixture of Penggaron River to quality of brick which yielded from as longas Penggaron River require to conducted research by giving addition raw material with differentsand mixture at each treatment of research covering; group without sand mixture, group with sandmixture 5 %, group with sand mixture 10 % and group with sand mixture 15 % so that from thetreatment each group can know the difference of its quality. With existence of sand mixture [at] clayraw material have positive and negative influence. When make-up the quality seen form physicallysand mixture will be more profit. But from strength, sand mixture will be more harm becauseexistence of sand mixture result degradation of strength depress. The result from analysis of sandmixture and clay raw material that taken from riverbank of Penggaron, hence mixing bestcomposition is 95% sand and 5% clay to be got quality in good shape, because having smalldecrease and transformation and reduction of its strength not too much. Beside